Editorial on combination treatment beyond sorafenib alone for hepatocellular carcinoma with portal vein tumor thrombosis - Bae, Sun Hyun; Park, Hee Chul (Translational Cancer Research; Vol 6, Supplement 3 (May 26, 2017): Translational Cancer Research, 2017)
Hepatocellular carcinoma (HCC) is one of the most common cancers worldwide and the third most common cause of cancer death with exceedingly high rates in Eastern/South-Eastern Asia, several areas of Africa and, historically, Southern Europe (1). Despite recent progress in screening programs and treatment for HCC, the prognosis is still poor because most cases are diagnosed at an advanced stage. The presence of portal vein tumor thrombosis (PVTT) in particular is considered an important prognostic factor of unfavorable survival. This is due to the combination of impaired hepatic reserves, intrinsic aggressiveness of the tumor, reduced tolerance to anti-neoplastic treatment, and a high rate of complications related to portal hypertension (2). The current practical guidelines for the treatment of advanced HCC including PVTT recommend sorafenib alone as the standard treatment but various treatment modalities are considered as alternative treatment options in the real world (3-9).